Products innovation in Islamic finance Workshop in Islamic Economics and Finance 2008 (WIEF'08) , Bilik Seminar, paras 2, Pusat Penerbitan dan percetakan, Lingkungan 2, Universiti Kebangsaaan Malaysia, 2-3 December 2008 - Workshop in Islamic Economics and Finance (2008 : Bangi, Selangor); Universiti Kebangsaan Malaysia. Fakulti Ekonomi dan Perniagaan (Bangi : Fakulti Ekonomi Dan Perniagaan, Universiti Kebangsaan Malaysia, 2008)
Seven session of working paper for workshop in Islamic Economics and Finance 2008
Title from container
System requirements: Adobe Acrobat Reader
Keywords: Finance -- Islamic countries -- Congresses; Finance -- Religious aspects -- Islam -- Congresses; Banks and banking -- Religious aspects -- Islam -- Congresses